2018
DOI: 10.2337/dc18-1512
|View full text |Cite
|
Sign up to set email alerts
|

Relative Pancreas Volume Is Reduced in First-Degree Relatives of Patients With Type 1 Diabetes

Abstract: OBJECTIVEPancreas size is reduced in patients at type 1 diabetes onset and in autoantibody (AAB)-positive donors without diabetes. We sought to determine whether pancreas volume (PV) imaging could improve understanding of the loss of pancreas size in first-degree relatives (FDRs) of patients with type 1 diabetes. We also examined relationships among PV, AAB status, and endocrine and exocrine functions. RESEARCH DESIGN AND METHODSWe conducted a cross-sectional study that included five groups: AAB 2 control subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 44 publications
5
105
3
Order By: Relevance
“…However, in this small cohort we did not detect an association of T reg turnover rate by F max with individual genetic variants in the IL2RA , IL2/IL21 and PTPN2 loci that have been associated with risk for T1D. Other studies also find phenotypical differences between unaffected relatives and controls; one report demonstrated that T1D family members have an elevated inflammatory state and another found small pancreas volume in family members compared with non‐family members as controls .…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…However, in this small cohort we did not detect an association of T reg turnover rate by F max with individual genetic variants in the IL2RA , IL2/IL21 and PTPN2 loci that have been associated with risk for T1D. Other studies also find phenotypical differences between unaffected relatives and controls; one report demonstrated that T1D family members have an elevated inflammatory state and another found small pancreas volume in family members compared with non‐family members as controls .…”
Section: Discussioncontrasting
confidence: 78%
“…The subjects were divided into four groups, with Ctrl = normal control, 0 = relatives without autoantibody, 1 = relatives with one autoantibody and ≥ 2 = relatives with two or more autoantibodies; n = 38 (two participants, including one from the 0 antibody group and one from the two or more antibodies group, were excluded from the analysis due to poor quality of T cell sorting). demonstrated that T1D family members have an elevated inflammatory state [11] and another found small pancreas volume in family members compared with non-family members as controls [12]. We previously demonstrated that individuals with clinically overt T1D had increased CD4 memory T cell turnover [6]; however, we did not find this in autoantibody-positive relatives of those with T1D, suggesting that increased CD4 proliferation only occurs later in disease progression.…”
Section: Discussioncontrasting
confidence: 59%
“…Thus, a third of the diabetic patients had abnormally low exocrine pancreas function, which could depend on previous mild pancreatitis and/or abnormally small pancreas as small pancreas size has been found to correlate with decrease exocrine function . The small size of pancreas in children who later get T1D might either depend on decreased insulin production with the secondary consequence of less growth of pancreas, or be a consequence of a genetic background, which is supported by the fact that the size of pancreas seems to be reduced also in relatives of patients with T1D . In some cases, the low amylase values could also be related to low food intake in connection with ketoacidosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies show that pancreas often is smaller in patients who develop T1D, although the same smaller size also is seen in first‐degree relatives of patients with T1D …”
Section: Introductionmentioning
confidence: 99%
“…Finally, in a recent study evaluating PV by MRI, Campbell‐Thompson ML et al described for the first time a significantly lower PV adjusted for BMI (PV‐to‐BMI ratio) in non‐diabetic T1D first‐degree relatives (FDRs) with or without one/multiple autoantibodies positivity compared with unrelated control subjects. Moreover, patients with recent‐onset T1D showed lower PV‐to‐BMI ratio compared with FDRs …”
Section: Pancreas Anatomical Alterations In T1dmentioning
confidence: 96%